Collaborative Governance Model in Managing International Borders in Riau Islands Province using Partial Least Squares Method - Adji Suradji Muhammad; Tulus Warsito; Ulung Pribadi; Achmad Nurmandi (Magister Ilmu Administrasi Publik, 2017)
Despite the large number of border management agencies at both local and national level, there is no guarantee that borders of Riau Islands Province are well protected. Most illegal fishing, mining and human trafficking are attributable to the lack of collaboration among various border management agencies. It also indicates failure to implement effectively collaborative culture, leadership, team process, structure, and strategic vision. This study aims to evaluate the implementation of Collaborative Governance Model in the management of Riau Islands Province borders. The study used a descriptive verification method, and collected data using an interview technique, while partial least squares method was used in analyzing the data. Results swhowed that the collaborative team process (CTP), turned out to be the dependent variable, while the other five principles, , inter alia, structural, cultural, leadership and strategic vision variables were established as the indepdendentindependent variables that influence CTP.